Tumor Phenotype and Gene Expression During Early Mammary Tumor Development in Offspring Exposed to Alcohol In Utero. (4th July 2016) - Crismale‐Gann, Catina; Stires, Hillary; Katz, Tiffany A.; Cohick, Wendie S.
Abstract : Background: Alcohol exposure in utero increases susceptibility to carcinogen‐induced mammary tumorigenesis in adult offspring and causes tumors with a more malignant phenotype. This study was conducted to identify changes early in tumor development that might lead to this outcome. Methods: Pregnant Sprague–Dawley rats were fed a liquid diet containing 6.7% ethanol (alcohol), an isocaloric liquid diet without alcohol (pair‐fed), or rat chow ad libitum (ad lib) from gestation day 7 until parturition. At birth, female progeny were cross‐fostered to control dams. Pups were weaned at postnatal day (PND) 21 and fed rat chow ad libitum for the remainder of the experiment. Female offspring were administered N ‐nitroso‐ N ‐methylurea (NMU; 50 mg/kg body weight) on PND 50. Mammary glands were palpated weekly, and offspring were euthanized at 16 weeks post‐NMU injection. Results: At 16 weeks post‐NMU, tumor multiplicity was greater in alcohol‐exposed offspring compared with control groups. Estrogen receptor‐ α (ER) mRNA expression was decreased in tumors from alcohol‐exposed offspring, and these animals developed more ER‐negative tumors relative to the pair‐fed group. Alcohol‐exposed offspring also tended to develop more progesterone receptor (PR)‐positive tumors. All tumors were HER2‐negative. PR positivity was associated with higher Ki67 expression, suggesting that PR‐positive tumors were more proliferative. Tumors from alcohol‐exposed animals exhibited increased mRNA expression of the insulin‐like growth factor (IGF) family members IGF‐II and IGFBP‐5. IGF‐II and DNA methyltransferase mRNA tended to be greater in the normal contralateral mammary glands of these animals. Conclusions: These data indicate that alcohol exposure in utero may shift NMU‐induced tumor development toward a more aggressive phenotype and that alterations in IGF‐II expression may contribute to these changes. Additional studies should be aimed at epigenetic mechanisms that underlie IGF‐II expression to further delineate how this gene is altered in mammary glands of adults exposed to alcohol in utero. Abstract : Alcohol exposure in utero increases mammary tumor susceptibility in adult rat offspring 23 weeks after carcinogen administration. The present work shows that at an earlier time point, tumors from alcohol‐exposed offspring exhibit markers indicative of more aggressive luminal tumors relative to controls. IGF‐II mRNA is increased in these tumors as well as in normal contralateral mammary glands. We conclude that fetal alcohol exposure promotes a more aggressive tumor phenotype and that alterations in IGF‐II expression may contribute to these changes.